QUALITY ENHANCEMENT NEEDS IN SELECTED PRIVATE HIGHER EDUCATION INSTITUTIONS AT THE PROVINCES IN CAMBODIA - Phan, Phallun (jfpublisher, 2025)
Cambodia's higher education institutions focus quality improvement. As a result, this research investigates quality enhancement for long-term growth at private higher education institutions (HEIs) in North-Eastern Cambodia, with a particular emphasis on graduate quality and labor market skill mismatches. The major purpose was to look at quality management components that encourage HEI quality improvement. A cross-sectional quantitative technique was used to collect data from 384 respondents. The theoretical framework specifies Quality Management, Quality in Education, Enhancement, Quality Assurance, and Quality Assessment, with an emphasis on curriculum standards, qualified individuals, and effective leadership. The findings revealed overwhelmingly positive perceptions of various quality management dimensions, including educational management, academic curriculum, academic staff and teaching strategies, student assessment, facilities and support staff, collaborations, financial management, internal quality assessment, and external quality assessment. Predictors accounted for 84.5% of the variation in HEI Quality Enhancement (R-squared =.845, p <.001). Student assessment had the most beneficial influence, followed by internal and external quality assessments, facilities and support personnel, and partnerships. Correlation analysis found significant dependency among these factors. A SWOT analysis identified strengths (internal quality assurance, leadership), weaknesses (resource constraints, data management), opportunities (external validation, collaboration), and threats (regulatory changes, economic pressures). This study highlights the need of quality improvement in Cambodian higher education institutions (HEIs), focusing on student evaluation, quality assurance, infrastructure, and strategic alliances. Future research should focus on multicollinearity, factors having non-significant effects, and bigger qualitative or comparative investigations.